Aqueous Manganese Dioxide Ink for Paper‐Based Capacitive Energy Storage Devices1. Issue 23 (17th April 2015) - Qian, Jiasheng; Jin, Huanyu; Chen, Bolei; Lin, Mei; Lu, Wei; Tang, Wing Man; Xiong, Wei; Chan, Lai Wa Helen; Lau, Shu Ping; Yuan, Jikang
Abstract: We report a simple approach based on a chemical reduction method to synthesize aqueous inorganic ink comprised of hexagonal MnO2 nanosheets. The MnO2 ink exhibits long‐term stability and continuous thin films can be formed on various substrates without using any binder. To obtain a flexible electrode for capacitive energy storage, the MnO2 ink was printed onto commercially available A4 paper pretreated with multiwalled carbon nanotubes. The electrode exhibited a maximum specific capacitance of 1035 F g −1 (91.7 mF cm −2 ). Paper‐based symmetric and asymmetric capacitors were assembled, which gave a maximum specific energy density of 25.3 Wh kg −1 and a power density of 81 kW kg −1 . The device could maintain a 98.9 % capacitance retention over 10 000 cycles at 4 A g −1 . The MnO2 ink could be a versatile candidate for large‐scale production of flexible and printable electronic devices for energy storage and conversion. Abstract : Printing the future : A simple chemical reduction method has been used to synthesize aqueous MnO2 ink that exhibits long‐term stability and can form continuous thin films on various substrates without the need for any binder. The as‐prepared MnO2 ink can also be coated onto conductive A4 paper to form capacitive energy storage devices.